1077 TELP In Urology: Hindrance or A Help During Covid-19 Pandemic? A Closed Loop Audit. (12th October 2021) - Henderson, L; Birse, E; Nalagatla, S; Reid, S
Abstract: Aim: TELP (Treatment Escalation/Limitation Plan) form is a novel clinical decision-making tool introduced during the COVID-19 pandemic in our health board to provide a standardised patient management plan in case of patient deterioration. A closed loop audit of its compliance in Urology patients was performed. Method: Patient medical records were analysed over two periods (Cycle 1: 5/10/20 - 11/10/20 and Cycle 2: 23/11/20 – 29/11/20) for all Urology patients in our institution. Cycle 1 audit findings were presented at the Departmental Education Meeting. During Cycle 1, an anonymous questionnaire was sent to all Urology Medical and Nursing staff to gather their opinion on TELP. Results: In total 100 patients were analysed. 66 were male and 34 females. Age ranged from 15 to 91 years. TELP form completion rate improved from 48% (Cycle 1) to 68% (Cycle 2), however, correct completion remained poor at 11.1% and 16.7% in Cycle 1 and Cycle 2 respectively. Commonly, there was no reporting of 'discussion with patient or family' or 'patient capacity'. Majority of patients with a completed TELP had one to four underlying co-morbidities and were emergency admissions (65%). The questionnaire reported barriers to compliance including, time for completion, document size, and the feeling it was inappropriate for certain patient groups. Most felt it did not represent patients' wishes (73%) or improved discussion regarding escalation status (50%). Conclusions: TELP forms have sub-optimal correct completion rates and may not always represent patient's wishes. Inherent barriers to its use need to be addressed, given limited resources during the COVID pandemic.